The emperor on the battlefield : Napoleon's worth as a military commander - Lotzin, Felix Christoph (Anchor Academic Pub., 2013)
Hauptbeschreibung This book seeks to explore two working hypotheses: Firstly, that Napoleon's alleged military superiority in terms of skill and battlefield competence over his peers can be empirically quantified and proven. Secondly, that the results of Napoleonic warfare can be predicted by applying the theory of Contest Success Functions to these battles. To address these claims this book is organized into four sections: Theory: The first of the conceptual sections summarizes the theoretical underpinning behind the economical understanding of conflict. This so called.